Pierre Trudeau, Organized Labour, and the Canadian Social Democratic Left, 1945-2000 - Aivalis, Christo (Queen's University, 2015)
This dissertation examines Pierre Elliott Trudeau’s relationship with labour unions and the Cooperative Commonwealth Federation-New Democratic Party of Canada from 1945 to 2000. Trudeau was an extremely influential historical figure, both as prime minister (1968-1984), but also before his entry into formal politics, when he traveled and studied around the world, became deeply influenced by leftist movements and intellectuals, and sought to modernize Quebec, which in his view was falling behind English Canada in terms of technological, social, and democratic development. In essence, Trudeau sought to forge a liberal democracy he thought absent in Quebec, and found his staunchest allies to be trade unionists and socialists. In the end, however, Trudeau largely abandoned those movements because he felt winning liberal freedoms required the shelving of socialist objectives. This would, in turn, be his justification for joining the Liberal Party in 1965. As Prime Minister, Trudeau opposed the objectives and philosophies of his former left allies, even as he maintained his image as a progressive. So while many saw his Just Society, his approach to public and Canadian ownership of energy, his New Society, and his Charter of Rights and Freedoms as left-wing initiatives, I argue that Trudeau’s actions were undertaken not to challenge capitalism, but to strengthen it, primarily through the empowerment of business and the disempowerment of unions and the economically-disenfranchised. Ultimately, this dissertation asserts that Trudeau cannot be classified as a socialist, but must be seen as a liberal preoccupied, not with liberty and equality, but with the continued pre-eminence of capitalist property relations.
Keywords: Canadian Labour Congress; Charter of Rights and Freedoms; Cooperative Commonwealth Federation; Foreign Investment Review Agency; Liberalism; National Energy Program; New Democratic Party; Organized Labour; Pierre Elliott Trudeau; Quiet Revolution; Socialism; Thesis; Wage and Price Controls